THE TECHNIQUE OF CONSTRUCTING A TETRAHEDRON MODEL USING A COMPASS AND RULER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This thesis presents geometric problems of gluing and cutting for the development of thinking.